APLIKASI PENGELOLAAN DATA KEPEGAWAIAN BERBASIS WEB PADA PT. PELAYARAN SAKTI INTI MAKMUR PALEMBANG - Novan Wijaya; Adelia Rizky Febriyanti; Anton Wibowo (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
PT. Pelayaran Sakti Inti Makmur is a express bahari fast boat operator company that has served people of Indonesia since 1990 until today in iall Indonesia waters. PT. Pelayaran Sakti Inti Makmur still uses a manual system such as recap data everyday, week and month. Manually, system often have errors in the recap process, both have the same data and even missing data. The application to be built aims to make it easier to manage staffing data at PT. Pelayaran Sakti Inti Makmur so that it becomes more effective and efficient. Staffing data includes calculating employee work period automatically, assisting in taking care of permits, leave, resignation, warning letters, and simplifying HRD in the process of making reports. Data collection techniques used were interviews, observation and literature study. System development methodology used is iterative method, which in iterative method includes the stages of analysis, design, program code creation and testing to describe proposed application using rich picture, DFD, Context Diagram, and ERD. This application is created using the PHP programming language and database management using MySQL.